Austenitic stainless steel sheet and method for producing same
The controlled chemical composition and annealing process of austenitic stainless steel sheets form a self-lubricating oxide scale, addressing the issue of high-temperature slidability in turbocharger parts by reducing friction and wear, enhancing performance in high-temperature environments.
Patent Information
- Application Number
- JP2020176631
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-21
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-10-21
AI Technical Summary
Existing austenitic stainless steels used in turbocharger parts suffer from inadequate high-temperature slidability due to issues like scale peeling and adhesion, which can lead to poor gas flow and mechanical wear, especially in high-temperature environments without lubrication.
Austenitic stainless steel sheets with controlled chemical compositions and specific annealing processes to form a self-lubricating oxide scale, ensuring a balanced ratio of elements like Cr, Mn, Si, and Al, and a maximum Mn concentration gradient to enhance high-temperature slidability.
The solution provides improved high-temperature slidability by forming a self-lubricating oxide scale that reduces friction and wear, maintaining performance in harsh automotive and industrial environments.
Smart Images

Figure 0007616857000006 
Figure 0007616857000007 
Figure 0007616857000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an austenitic stainless steel sheet and a method for producing the same. [Background technology]
[0002] Among automotive parts, exhaust parts are required to stably ventilate high-temperature exhaust gas. In addition, exhaust parts are used in an environment where corrosion is accelerated by condensation water generated by cooling of exhaust gas. For this reason, materials with excellent heat resistance, represented by oxidation resistance, high-temperature strength, and thermal fatigue properties, and corrosion resistance are used for exhaust parts.
[0003] One example of an exhaust part is a turbocharger part. In recent years, turbochargers have been often installed in automobiles from the viewpoints of improving fuel efficiency, reducing engine displacement (also called "downsizing"), and optimizing engine displacement (also called "rightsizing").
[0004] For this reason, heat-resistant austenitic stainless steel, which has excellent heat resistance and corrosion resistance, is used as the material for turbocharger parts. For example, Patent Documents 1 to 4 disclose austenitic stainless steels intended for use in turbochargers. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2014 / 157655 [Patent Document 2] JP 2017-14538 A [Patent Document 3] JP 2017-160493 A [Patent Document 4] JP 2019-143186 A Summary of the Invention [Problem to be solved by the invention]
[0006] In addition, some turbocharger parts are used in high-temperature, non-lubricated conditions where friction occurs repeatedly. In this case, it is possible that parts in contact with each other wear out and adhere to each other in the operating environment. As a result, for example, vanes and valves for adjusting the flow rate of exhaust gas inside the turbocharger may have problems opening and closing, resulting in poor gas flow.
[0007] Therefore, turbocharger parts are also required to have high-temperature sliding properties, which are friction and wear resistance at high temperatures. In particular, from the viewpoints of efficiency improvement and reduction of environmental load, in the situation where the temperature of exhaust gas passing through turbochargers is becoming higher, friction and adhesion between parts are likely to occur.
[0008] However, the austenitic stainless steels disclosed in Patent Documents 1 to 3 have not been sufficiently studied with respect to high-temperature sliding properties. Therefore, there is room for further improvement in high-temperature sliding properties. In addition, the austenitic stainless steels disclosed in Patent Document 4 have high Mn and Cu contents, and have relatively good high-temperature sliding properties. On the other hand, when the usage environment becomes even hotter and a thick scale is formed, the scale may easily peel off. In a usage environment where heating and cooling are repeated, the scale peeling and regeneration are repeated, and the surface unevenness becomes large. As a result, adhesion between parts may easily occur, and high-temperature sliding properties may decrease.
[0009] In view of the above, an object of the present invention is to solve the above problems and to provide an austenitic stainless steel sheet having good high-temperature sliding properties and a method for producing the same. [Means for solving the problem]
[0010] The present invention has been made to solve the above-mentioned problems, and the gist of the present invention is the following austenitic stainless steel sheet and a manufacturing method thereof.
[0011] (1) Chemical composition, in mass%, C: 0.005-0.30%, Si: 1.00-4.00%, Mn: 0.90-8.00%, P: 0.01-0.05%, S: 0.0001 to 0.01%, Ni: 5.0-15.0%, Cr: 19.50~26.00%, N: 0.02-0.40%, Al: 0.001 to 0.50%, Cu: 0-3.0%, REM: 0~0.100%, Mo: 0-2.0%, V: 0-1.0%, Ti: 0 to 0.30%, Nb: 0-0.30%, B: 0~0.005%, Ca: 0 to 0.010%, W: 0-3.0%, Zr: 0-0.30%, Sn: 0-0.50%, Co: 0-0.30%, Mg: 0 to 0.010%, Sb: 0-0.50%, Ga: 0 to 0.30%, Ta: 0 to 1.0%, Hf: 0-1.0%, Bi: 0 to 0.02%, The balance is Fe and impurities. An austenitic stainless steel sheet satisfying the following formulas (i) and (ii): 11.5≦(Cr+Mn) / (Si+Al)≦15.0 (i) 0.80≦X / Y≦1.00 (ii) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero, and each symbol in the above formula is defined as follows. X: Maximum Mn concentration (mass%) in the region from the surface to a depth of 1.0 μm in the sheet thickness direction Y: Mn concentration (mass%) at a depth of 10.0 μm from the surface in the sheet thickness direction
[0012] (2) The chemical composition is, in mass%, Cu: 0.01-3.0%, REM: 0.0001~0.100%, Mo: 0.1-2.0%, V: 0.05-1.0%, Ti: 0.005 to 0.30%, Nb: 0.005-0.30%, B: 0.0002~0.005%, Ca: 0.0005~0.010%, W: 0.1-3.0%, Zr: 0.05-0.30%, Sn: 0.01 to 0.50%, Co: 0.03 to 0.30%, Mg: 0.0002~0.010%, Sb: 0.005 to 0.50%, Ga: 0.0002 to 0.30%, Ta: 0.001 to 1.0%, Hf: 0.001 to 1.0%, and Bi: 0.001 to 0.02%, The austenitic stainless steel sheet according to the above (1), comprising one or more selected from the following:
[0013] (3) An austenitic stainless steel sheet according to (1) or (2) above, in which, after being held in air at 850°C for 1 hour, a pin-on-disk friction and wear test is performed under conditions of a load of 0.5 N and a test distance of 20 m, the average wear scar depth is 5.0 μm or less.
[0014] (4) The austenitic stainless steel sheet according to any one of (1) to (3) above, which is used for turbocharger parts.
[0015] (5) An exhaust part using the austenitic stainless steel sheet according to any one of (1) to (4) above.
[0016] (6) A method for producing an austenitic stainless steel sheet according to any one of the above (1) to (5), comprising carrying out an annealing heat treatment in a temperature range of 1140 to 1250° C. for 5 to 60 seconds. Effect of the Invention
[0017] According to the present invention, an austenitic stainless steel sheet having good high-temperature sliding properties can be obtained. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a graph showing the relationship between the wear scar depth after a high-temperature sliding test and (Cr+Mn) / (Si+Al). [Diagram 2] FIG. 2 is a diagram showing a schematic diagram of the change in Mn concentration. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present inventors have conducted detailed studies on the high-temperature sliding properties of austenitic stainless steel sheets and have obtained the following findings (a) to (c).
[0020] (a) The temperature range in which turbochargers are used is high, and therefore thick scale forms in the operating environment. The present inventors therefore focused on this oxide scale in order to improve high-temperature sliding properties. Depending on the oxide scale that is formed, when parts rub against each other, it transfers to the sliding surfaces and reduces the coefficient of friction, resulting in a so-called self-lubricating effect. When this self-lubricating effect occurs, high-temperature sliding properties are improved. Therefore, it is desirable to form a scale that has a self-lubricating effect.
[0021] (b) For example, when a scale containing oxides such as Si-based oxides and Mn-based oxides is formed, a self-lubricating effect occurs. On the other hand, the present inventors have clarified that when a scale containing a large amount of Mn-based oxides is formed, the formed scale becomes thick and may become more likely to peel off. And, even in the part where the scale has peeled off, a self-lubricating effect occurs, but such a part has a large surface unevenness, so that the high-temperature sliding property is easily deteriorated over time.
[0022] (c) Therefore, the inventors have clarified that it is effective to control the Mn concentration in the scale within an appropriate range, and to control the Cr concentration, which is effective in forming a scale having a self-lubricating effect, and the Si and Al concentrations, which contribute to improving high-temperature sliding properties in the scale. In order to control the concentrations of these elements in the scale, it is preferable to set the contents of the above elements in the steel within an appropriate range, and to perform annealing heat treatment after cold rolling at a relatively high temperature for a short period of time.
[0023] The present invention has been made based on the above findings. Each of the features of the present invention will be described in detail below.
[0024] 1.Chemical composition The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."
[0025] C: 0.005 to 0.30% C is an element that stabilizes the austenite structure and improves high-temperature strength and high-temperature sliding properties. It is also an element necessary for ensuring high-temperature hardness. For this reason, the C content is set to 0.005% or more. From the viewpoint of high-temperature sliding properties and manufacturing costs, the C content is preferably set to 0.030% or more, and more preferably set to 0.050% or more. However, if C is contained in excess, work hardening is likely to occur. In addition, excess C combines with Cr to form Cr carbides, thereby reducing corrosion resistance and intergranular corrosion properties. For this reason, the C content is set to 0.30% or less. From the viewpoint of hot workability, the C content is preferably set to 0.20% or less, and more preferably set to 0.19% or less.
[0026] Si: 1.00-4.00% Si has a deoxidizing effect. In addition, the internal oxidation of Si makes it difficult for scale to peel off, and as a result, high-temperature sliding properties are improved. In other words, the internal oxidation of Si contributes to improving high-temperature sliding properties by improving high-temperature strength and high-temperature hardness. For this reason, the Si content is set to 1.00% or more. To further improve high-temperature sliding properties, the Si content is preferably set to 1.20% or more, and more preferably set to 1.50% or more.
[0027] However, if too much Si is contained, the steel sheet becomes excessively hard, and the part workability and manufacturability are deteriorated. Therefore, the Si content is set to 4.00% or less. From the viewpoints of manufacturing cost, pickling property, and solidification cracking during welding, the Si content is preferably set to 3.00% or less, and more preferably set to 2.80% or less.
[0028] Mn: 0.90-8.00% Mn has a deoxidizing effect. In addition, Mn has the effect of stabilizing the austenite structure and improving scale adhesion. Furthermore, the inclusion of Mn gives the scale a self-lubricating effect and a self-repairing function, which leads to improved high-temperature sliding properties. For this reason, the Mn content is set to 0.90% or more.
[0029] However, if the Mn content exceeds 8.00%, thick scale will be formed in the usage environment. As a result, the scale will be easily peeled off, and the surface unevenness will increase, which may result in a decrease in high-temperature sliding properties. In addition, it is considered that the inclusion cleanability and pickling property will be significantly decreased, and the product surface will become rough. For this reason, the Mn content is set to 8.00% or less. From the viewpoint of inclusion cleanability and pickling property, the Mn content is preferably set to the range of 0.90 to 1.50%. In addition, if it is desired to further improve the high-temperature sliding properties, the Mn content is preferably set to the range of 1.85 to 8.00%.
[0030] P: 0.01-0.05% P is an element that promotes hot workability and solidification cracking during manufacturing. For this reason, the P content is set to 0.05% or less. The P content is preferably set to 0.04% or less. A lower P content is preferable, but excessive reduction of P increases refining costs. For this reason, the P content is set to 0.01% or more. Furthermore, from the viewpoint of reducing refining costs, the P content is preferably set to 0.02% or more.
[0031] S: 0.0001 to 0.01% S is an element that reduces hot workability and corrosion resistance. Furthermore, when coarse sulfides such as MnS are formed, the inclusion cleanliness of the steel sheet is significantly reduced. For this reason, the S content is set to 0.01% or less. From the viewpoint of oxidation resistance, the S content is more preferably set to 0.005% or less. However, excessive reduction of S increases refining costs. For this reason, the S content is set to 0.0001% or more. From the viewpoint of refining costs, the S content is preferably set to 0.0005% or more.
[0032] Ni: 5.0~15.0% Ni is an element that stabilizes the austenite structure and improves corrosion resistance and oxidation resistance. For this reason, the Ni content is set to 5.0% or more. From the viewpoints of high-temperature strength, corrosion resistance, and manufacturability, the Ni content is preferably set to 9.0% or more. However, excessive Ni content increases the manufacturing cost and hardens the material. For this reason, the Ni content is set to 15.0% or less. The Ni content is preferably set to 14.0% or less.
[0033] Cr: 19.50~26.00% Cr is an element that improves corrosion resistance, oxidation resistance, and high-temperature sliding properties. From the viewpoint of suppressing abnormal oxidation in an exhaust part environment, the Cr content is set to 19.50% or more. The Cr content is preferably set to 20.00% or more, and more preferably set to 20.50% or more. However, if Cr is contained in excess, the material becomes hard and the manufacturing cost increases. For this reason, the Cr content is set to 26.00% or less. Furthermore, from the viewpoints of workability, manufacturability, and manufacturing cost, the Cr content is preferably set to 25.30% or less, and more preferably set to 24.00% or less.
[0034] N: 0.02 to 0.40% Like C, N stabilizes the austenite structure. It is also an effective element for improving high-temperature strength, high-temperature hardness, and high-temperature sliding properties. In particular, it acts as a solid solution strengthening element to improve high-temperature strength. For this reason, the N content is set to 0.02% or more. In order to improve high-temperature sliding properties, the N content is preferably more than 0.05%, more preferably 0.10% or more, and even more preferably 0.20% or more.
[0035] However, if the N content exceeds 0.40%, the room temperature material becomes significantly hard. As a result, the cold workability during steel plate manufacturing deteriorates, and part workability decreases. For this reason, the N content is set to 0.40% or less. From the viewpoint of suppressing pinholes and intergranular corrosion of welds during welding, the N content is preferably set to 0.33% or less.
[0036] Al: 0.001 to 0.50% Al acts as a deoxidizing element and improves inclusion cleanliness. In addition, Al improves scale adhesion, suppresses the spalling of oxide scale, and improves high-temperature sliding properties. For this reason, the Al content is set to 0.001% or more. The Al content is preferably set to 0.010% or more, and more preferably set to 0.040% or more.
[0037] However, Al is a ferrite-forming element, and if it is contained in an amount exceeding 0.50%, it reduces the stability of the austenite structure. Furthermore, not only does it reduce the pickling property, but it also increases the amount of inclusions, which deteriorates the surface properties. For this reason, the Al content is set to 0.50% or less. From the viewpoint of surface properties, the Al content is preferably set to 0.30% or less. Moreover, from the viewpoint of hot workability, the Al content is preferably set to 0.10% or less.
[0038] Among the above elements, it is necessary to control the content of each of Cr, Mn, Si, and Al, which affect the scale formed in the usage environment. Among the above elements, Cr and Mn constitute the outside of the scale, i.e., the outer layer scale, in the usage environment. This outer layer scale tends to grow thick, but when it has an appropriate thickness, it improves high-temperature sliding properties due to its self-lubricating action. On the other hand, Si and Al constitute the base steel sheet side of the scale, i.e., the inner layer scale. This inner layer scale tends to form thin. And since it contains oxides of Si and Al and hardens the base steel sheet, it improves high-temperature sliding properties and improves oxidation resistance.
[0039] Therefore, by controlling the relationship between the contents of Cr and Mn, which thicken the scale, and the contents of Si and Al, which thin the scale, within an appropriate range and controlling the thickness of the scale so that it does not become too thick, it is possible to maintain good high-temperature sliding properties. Figure 1 is a diagram showing the relationship between the wear scar depth after high-temperature sliding tests and (Cr+Mn) / (Si+Al) for austenitic stainless steels containing 19-25% Cr, 9-20% Ni, 0.5-3.3% Si, 0.8-8.4% Mn, and 0.01-0.04% Al.
[0040] The numbers in parentheses next to each plot in Figure 1 indicate the thickness of the scale (µm). The scale was defined as a blackish-gray layer in which 25% (mass%) or more of O was detected by SEM / EDS analysis of the sliding surface side. Figure 1 shows that the wear scar depth after the high-temperature sliding test is 5 µm or less, and high-temperature sliding properties are good when (Cr+Mn) / (Si+Al) is in the range of 11.5 to 15.0, and in this case, the thickness of the scale is also relatively thin.
[0041] Therefore, the respective contents of Cr, Mn, Si and Al must satisfy the following formula (i). 11.5≦(Cr+Mn) / (Si+Al)≦15.0 (i) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, the value is set to zero.
[0042] If the value in equation (i) is less than 11.5, the scale will be thin, but the high-temperature sliding properties will be poor. For this reason, the value in equation (i) is set to 11.5 or more. It is preferable that the value in equation (i) is set to 11.8 or more. On the other hand, if the value in equation (i) exceeds 15.0, the scale will be too thick and the scale will be prone to peeling. As a result, in a high-temperature, long-term usage environment, the high-temperature sliding properties will deteriorate. For this reason, the value in equation (i) is set to 15.0 or less. It is preferable that the value in equation (i) is set to 14.0 or less.
[0043] In addition to the above elements, one or more elements selected from Cu, REM, Mo, V, Ti, Nb, B, Ca, W, Zr, Sn, Co, Mg, Sb, Ga, Ta, Hf, and Bi may be contained within the ranges shown below. The reasons for limiting each element will be explained.
[0044] Cu: 0-3.0% Cu has the effect of stabilizing austenite and improving oxidation resistance. In addition, Cu also has the effect of imparting a self-lubricating action and a self-repairing function to the scale and improving high-temperature sliding properties. For this reason, Cu may be contained as necessary. However, excessive Cu content will actually decrease oxidation resistance and manufacturability. Therefore, the Cu content is set to 3.0% or less. From the viewpoint of manufacturability, the Cu content is preferably set to 2.8% or less, and more preferably set to 2.5% or less. On the other hand, in order to obtain the above effect, the Cu content is preferably set to 0.01% or more, and more preferably set to 0.10% or more. From the viewpoint of corrosion resistance, the Cu content is more preferably set to 0.20% or more.
[0045] REM: 0~0.100% REM (rare earth elements) have the effect of improving oxidation resistance and thereby improving high-temperature sliding properties. For this reason, they may be included as necessary. However, if REM is included in excess, oxides containing REM are formed in the nozzle through which molten steel flows during casting, causing nozzle blockage, or sulfides containing REM are formed, reducing corrosion resistance. For this reason, the REM content is set to 0.100% or less. From the viewpoint of manufacturing costs, the REM content is preferably set to 0.090% or less. On the other hand, in order to obtain the above effect, the REM content is preferably set to 0.0001% or more, and more preferably set to 0.0010% or more.
[0046] REM refers to a total of 17 elements including Sc, Y and lanthanides, and the above REM content refers to the total content of these elements. In industry, REM is often added in the form of misch metal.
[0047] Mo: 0-2.0% Mo is an element that improves corrosion resistance. Mo also has the effect of improving high-temperature strength. When Mo is contained, in addition to solid solution strengthening, precipitation strengthening occurs by precipitating Mo carbides. Furthermore, the formation of precipitates can improve wear resistance, i.e., high-temperature sliding properties. For this reason, Mo may be contained as necessary. However, Mo is an expensive element, and if it is contained in excess, the manufacturing cost increases. Therefore, the Mo content is set to 2.0% or less. From the viewpoint of inclusion cleanliness, the Mo content is preferably set to 1.7% or less. On the other hand, in order to obtain the above effect, the Mo content is preferably set to 0.1% or more.
[0048] V: 0 to 1.0% V has the effect of improving corrosion resistance. In addition, V forms carbides and has the effect of improving high-temperature strength and wear resistance, i.e., high-temperature sliding properties. For this reason, V may be contained as necessary. However, excessive V content increases the manufacturing cost and decreases the abnormal oxidation limit temperature. For this reason, the V content is set to 1.0% or less. From the viewpoint of manufacturability and inclusion cleanliness, the V content is preferably set to 0.8% or less. On the other hand, in order to obtain the above effect, the V content is preferably set to 0.05% or more.
[0049] Ti: 0 to 0.30% Ti combines with C and N to improve corrosion resistance and intergranular corrosion resistance. Therefore, Ti may be contained as necessary. However, if Ti is contained in an amount exceeding 0.30%, nozzle clogging is likely to occur during the casting stage, and manufacturability is significantly reduced. Therefore, the Ti content is set to 0.30% or less. From the viewpoint of manufacturing costs, the Ti content is preferably set to 0.20% or less. On the other hand, in order to obtain the above effects, the Ti content is preferably set to 0.005% or more. From the viewpoints of high temperature strength and intergranular corrosion resistance of welds, the Ti content is more preferably set to 0.010% or more.
[0050] Nb: 0 to 0.30% Like Ti, Nb combines with C and N to improve corrosion resistance and intergranular corrosion resistance. In addition, Nb also has the effect of improving high-temperature strength and high-temperature sliding properties. For this reason, Nb may be contained as necessary. However, if Nb is contained in an amount exceeding 0.30%, hot workability is significantly reduced. For this reason, the Nb content is set to 0.30% or less. From the viewpoint of manufacturing costs, the Nb content is preferably set to less than 0.15%. On the other hand, in order to obtain the above effects, the Nb content is preferably set to 0.005% or more. From the viewpoint of high-temperature strength and intergranular corrosion properties of welds, the Nb content is preferably set to 0.010% or more.
[0051] B: 0~0.005% B has the effect of improving hot workability. It also has the effect of improving oxidation resistance. Therefore, it may be contained as necessary. However, if B is contained in excess, borocarbide is formed. This reduces the inclusion cleanliness and intergranular corrosion resistance of the steel sheet. For this reason, the B content is set to 0.005% or less. From the viewpoint of ductility, the B content is preferably set to 0.002% or less. On the other hand, in order to obtain the above effect, the B content is preferably set to 0.0002% or more. From the viewpoint of refining costs, the B content is more preferably set to 0.0003% or more.
[0052] Ca: 0 to 0.010% Ca has a desulfurization effect, so it may be contained as necessary. However, if Ca is contained in an amount exceeding 0.010%, water-soluble inclusions CaS are formed. As a result, the inclusion cleanliness and corrosion resistance of the steel sheet are significantly reduced. For this reason, the Ca content is set to 0.010% or less. From the viewpoint of surface properties, the Ca content is preferably set to 0.003% or less. On the other hand, in order to obtain the above effect, the Ca content is preferably set to 0.0005% or more. Furthermore, from the viewpoint of manufacturability, the Ca content is more preferably set to 0.0010% or more.
[0053] W: 0~3.0% W has the effect of improving high-temperature strength and corrosion resistance, and may be contained as necessary. However, if W is contained in an amount exceeding 3.0%, it leads to hardening of the steel plate, deterioration of toughness during manufacturing, and increased manufacturing costs. For this reason, the W content is set to 3.0% or less. Furthermore, from the viewpoint of manufacturability and refining costs, the W content is preferably set to 2.0% or less. On the other hand, in order to obtain the above effect, the W content is preferably set to 0.1% or more.
[0054] Zr: 0 to 0.30% Zr combines with C or N to improve the intergranular corrosion resistance and oxidation resistance of the weld. Therefore, Zr may be contained as necessary. However, if Zr is contained in an amount exceeding 0.30%, it leads to a significant decrease in manufacturability and an increase in manufacturing costs. For this reason, the Zr content is set to 0.30% or less. From the viewpoint of manufacturability and refining costs, the Zr content is preferably set to 0.10% or less. On the other hand, in order to obtain the above effect, the Zr content is preferably set to 0.05% or more.
[0055] Sn: 0 to 0.50% Sn has the effect of improving corrosion resistance and high-temperature strength, so it may be contained as necessary. However, if Sn is contained in an amount exceeding 0.50%, slab cracks may occur during production. For this reason, the Sn content is set to 0.50% or less. Furthermore, from the viewpoint of manufacturability and refining costs, the Sn content is preferably set to 0.30% or less. On the other hand, in order to obtain the above effect, the Sn content is preferably set to 0.01% or more, more preferably set to 0.03% or more, and even more preferably set to 0.05% or more.
[0056] Co: 0 to 0.30% Co has the effect of improving high-temperature strength, and may be contained as necessary. However, if Co is contained in an amount exceeding 0.30%, the steel plate becomes hard, the toughness during manufacturing decreases, and manufacturing costs increase. For this reason, the Co content is set to 0.30% or less. In consideration of manufacturability and refining costs, the Co content is preferably set to 0.20% or less. On the other hand, in order to obtain the above effect, the Co content is preferably set to 0.03% or more.
[0057] Magnesium: 0 to 0.010% Mg has a deoxidizing effect. In addition, Mg has the effect of refining or dispersing the slab structure with oxides, thereby refining the steel sheet structure and improving the inclusion cleanliness. For this reason, Mg may be contained as necessary. However, excessive Mg content reduces weldability and corrosion resistance. In addition, the formation of coarse Mg inclusions reduces part workability. For this reason, the Mg content is set to 0.010% or less. Considering the refining cost, the Mg content is preferably set to 0.005% or less. On the other hand, in order to obtain the above effect, the Mg content is preferably set to 0.0002% or more. The Mg content is more preferably set to 0.0003% or more.
[0058] Sb: 0 to 0.50% Sb has the effect of improving high-temperature strength by segregating at grain boundaries. Therefore, it may be contained as necessary. However, if Sb is contained in an amount exceeding 0.50%, segregation occurs, and cracks occur during welding. Therefore, the Sb content is set to 0.50% or less. In consideration of high-temperature properties and manufacturing costs, the Sb content is preferably set to 0.30% or less, and more preferably set to 0.20% or less. On the other hand, in order to obtain the above effect, the Sb content is preferably set to 0.005% or more. In consideration of toughness, the Sb content is more preferably set to 0.030% or more, and even more preferably set to 0.050% or more.
[0059] Ga: 0 to 0.30% Ga may be contained as necessary to improve corrosion resistance and suppress hydrogen embrittlement. However, if Ga is contained in an amount exceeding 0.30%, coarse sulfides are generated, and part workability is reduced. For this reason, the Ga content is set to 0.30% or less. On the other hand, in order to obtain the above effects, the Ga content is preferably set to 0.0002% or more. Furthermore, from the viewpoint of manufacturability and manufacturing costs, the Ga content is more preferably set to 0.0020% or more.
[0060] Ta: 0 to 1.0% Hf: 0~1.0% Bi: 0 to 0.02% Ta has the effect of improving high-temperature strength, and may be contained as necessary. However, excessive inclusion of Ta increases manufacturing costs, so the Ta content is set to 1.0% or less. On the other hand, in order to obtain the above effect, the Ta content is preferably set to 0.001% or more. In order to further increase the strength, the Ta content is more preferably set to 0.010% or more. For the same reason, the Hf content is set to 1.0% or less. Also, for the same reason, the Hf content is preferably set to 0.001% or more, and more preferably set to 0.010% or more.
[0061] For the same reason, Bi may be contained as necessary. However, excessive Bi content increases the manufacturing cost. Therefore, the Bi content is set to 0.02% or less. On the other hand, in order to obtain the same effect as above, the Bi content is preferably set to 0.001% or more.
[0062] In the chemical composition of the present invention, the balance is Fe and impurities. Here, "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes when industrially manufacturing austenitic stainless steel sheets, and are acceptable within a range that does not adversely affect the present invention. It is desirable to reduce general harmful elements such as As and Pb and impurity elements as much as possible.
[0063] 2.Maximum Mn concentration In the austenitic stainless steel sheet according to the present invention, it is desirable to form a scale containing Mn by oxidation in the usage environment. This is because this scale exerts a self-lubricating effect and a self-repairing function in the usage environment, and improves high-temperature sliding properties. For this reason, it is necessary that a sufficient amount of Mn is present near the surface of the steel sheet before use.
[0064] Here, simply increasing the Mn content is insufficient from the viewpoint of improving high-temperature sliding properties in order to ensure a sufficient amount of Mn near the surface of the steel sheet before use, because the scale formed during use may become thicker and may not satisfy formula (i).
[0065] Normally, in austenitic stainless steel, before use, thick scales are not formed after pickling, and the Mn concentration near the surface is not constant due to the effects of diffusion, etc. Specifically, as shown in Figure 2, the Mn concentration increases as you move from the outermost surface in the plate thickness direction. Then, at a depth of about 10.0 μm in the plate thickness direction, the increase in Mn concentration becomes gentler and the value approaches the Mn content of the steel, i.e., the average composition.
[0066] Therefore, the maximum Mn concentration in the region from the surface to a depth of 1.0 μm in the sheet thickness direction, which is the Mn concentration near the surface, is specified as a requirement, relative to the Mn concentration at a depth of 10.0 μm from the surface in the sheet thickness direction, where the increase in Mn concentration is gradual. That is, the austenitic stainless steel sheet according to the present invention must satisfy the following formula (ii). The maximum Mn concentration is measured in the region from the surface to a depth of 1.0 μm in the sheet thickness direction. The reason for this is that in the region from the surface to a depth of 1.0 μm in the sheet thickness direction, the concentration does not increase at a constant rate but fluctuates, and if sufficient enrichment of Mn occurs up to 1.0 μm, high-temperature sliding properties can be improved.
[0067] 0.80≦X / Y≦1.00 (ii) In the above formula, each symbol is defined as follows. X: Maximum Mn concentration (mass%) in the region from the surface to a depth of 1.0 μm in the sheet thickness direction Y: Mn concentration (mass%) at a depth of 10.0 μm from the surface in the sheet thickness direction
[0068] (ii) If the ratio X / Y in the formula is less than 0.80, a good scale exhibiting self-lubricating action and self-repairing function is not formed. As a result, high-temperature sliding properties cannot be improved. For this reason, X / Y is set to 0.80 or more. X / Y is preferably set to 0.85 or more. On the other hand, if X / Y exceeds 1.00, Mn is excessively concentrated in the scale, and the scale becomes thick. As a result, high-temperature sliding properties are deteriorated. For this reason, X / Y is set to 1.00 or less. X / Y is preferably set to 0.95 or less.
[0069] Here, the above-mentioned X and Y may be measured by the following procedure. Specifically, the steel sheet surface from which the scale formed during annealing has been removed is degreased by pickling, and the concentrations of Mn, Fe, Cr, Si, Ni, Al, N, C, and O are analyzed from the steel sheet surface in the sheet thickness depth direction using a glow discharge optical emission spectrometer, and the maximum Mn concentration up to a depth position of 1.0 μm and the concentration at a depth position of 10.0 μm are calculated. Here, the Mn concentration is the analyzed concentration of Mn when the sum of all the above analyzed elements is taken as 100%.
[0070] 3. Evaluation of high-temperature sliding properties In the austenitic stainless steel sheet according to the present invention, the high-temperature sliding properties are evaluated by a pin-on-disk friction and wear test at 850°C. In the pin-on-disk friction and wear test, the test material is held in a furnace at 850°C in air for 1 hour. After that, the pin and the disk are brought into contact in the furnace at 850°C, and the test material is rotated around a circumference with a rotation diameter of 20 mm for a test distance of 20 m at a load of 0.5 N and a sliding speed of 3.3 mm / s.
[0071] After the test, the wear scar depth on the surface of the disk material is measured using a laser microscope. The wear scar depth is the difference between the non-contact portion of the pin and disk and the contact portion, and is the largest value. If the average value of the measured wear scar depths at six points (hereinafter simply referred to as the "average wear scar depth") is 5.0 μm or less, the high-temperature sliding properties are judged to be good, and if the average wear scar depth exceeds 5.0 μm, the high-temperature sliding properties are judged to be poor.
[0072] 4.Applications The austenitic stainless steel sheet according to the present invention is particularly suitable for use in exhaust parts, particularly turbocharger parts, such as nozzle parts and valve parts made up of precision parts, such as a nozzle mount, a nozzle plate, a nozzle ring, a nozzle vane, a drive ring, a drive lever, a lever plate, a shroud, and a wastegate valve.
[0073] 5. Manufacturing method A preferred method for producing the austenitic stainless steel sheet according to the present invention will now be described. It has been confirmed that the austenitic stainless steel sheet according to the present invention can be produced by, for example, the following production method, regardless of the production method.
[0074] The austenitic stainless steel sheet according to the present invention is preferably produced through a process including steelmaking-hot rolling-annealing and pickling or steelmaking-hot rolling-annealing and pickling-cold rolling-annealing and pickling as follows.
[0075] 5-1.Steelmaking process It is preferable to melt steel having the above-mentioned chemical composition in an electric furnace or converter, and then perform secondary refining. The melted steel is made into a slab by a known casting method (continuous casting, etc.). The thickness of the slab to be produced may be appropriately set depending on the subsequent rolling conditions, etc.
[0076] 5-2.Hot rolling process The obtained slab is then heated at 1200 to 1300° C. and preferably hot-rolled by continuous rolling until the desired thickness is reached. The slab is hot-rolled to a hot-rolled sheet. The reduction ratio during hot rolling may be appropriately selected.
[0077] After hot rolling, the hot-rolled sheet is generally subjected to hot-rolled sheet annealing and pickling treatment, but the hot-rolled sheet annealing may be omitted. When hot-rolled sheet annealing is performed, the annealing temperature is preferably in the range of 1100 to 1200°C, and the annealing time is preferably in the range of 10 to 60 seconds.
[0078] 5-3.Cold rolling process Thereafter, it is preferable to perform cold rolling to obtain a cold-rolled sheet having a predetermined thickness. The reduction ratio during hot rolling may be appropriately selected.
[0079] 5-4.Cold-rolled sheet annealing process Next, it is preferable to subject the obtained cold-rolled sheet to a cold-rolled sheet annealing heat treatment (hereinafter simply referred to as "annealing"). Mn diffuses into the scale formed during annealing of the cold-rolled sheet, and the Mn concentration decreases at the interface between the scale formed during annealing and the base material. This area of reduced Mn concentration appears on the steel sheet surface by pickling after annealing. That is, the Mn concentration near the surface decreases, making it difficult to satisfy formula (ii). If the Mn concentration near the surface (also referred to as the "surface layer") is reduced when used as a turbocharger part, there is a risk that the formation of a scale having self-lubricating and self-repairing functions will be inhibited, resulting in reduced high-temperature sliding properties.
[0080] Table 1 shows the Mn concentration when the annealing conditions are changed for an austenitic stainless steel containing 19% Cr, 13% Ni, and 3% Si. When the cold-rolled sheet annealing conditions are changed to high temperature and short time conditions, such as 1120°C for 60 seconds to 1180°C for 30 seconds, the maximum Mn concentration in the region from the surface to a depth of 1.0 μm in the sheet thickness direction increases from 0.63% to 0.88%, suppressing the decrease in Mn concentration in the surface layer. As a result, high-temperature sliding properties can be improved.
[0081] [Table 1]
[0082] Therefore, as is clear from Table 1, it is preferable to anneal at a high temperature for a short time so as not to cause a decrease in the Mn concentration. This is because annealing at a high temperature for a short time suppresses the decrease in the Mn concentration in the surface layer and allows a steel sheet to be obtained with a structure in which recrystallization is completed.
[0083] Specifically, the annealing temperature when annealing the cold-rolled sheet is preferably in the temperature range of 1140 to 1250 ° C. If the annealing temperature is less than 1140 ° C, recrystallization does not occur sufficiently, and sufficient high-temperature strength cannot be obtained. In addition, high-temperature sliding properties are also reduced. For this reason, the annealing temperature is preferably 1140 ° C or higher. On the other hand, if the annealing temperature exceeds 1250 ° C, the diffusion of Mn is excessively promoted, and as a result, the Mn concentration is reduced at the interface between the scale formed after annealing and the base material. As a result, the formula (ii) cannot be satisfied, and high-temperature sliding properties are reduced. For this reason, the annealing temperature is preferably 1250 ° C or lower, and more preferably 1190 ° C or lower.
[0084] Also, the annealing time is preferably 5 to less than 60 seconds. If the annealing time is less than 5 seconds, recrystallization does not occur sufficiently, and sufficient high-temperature strength cannot be obtained. In addition, high-temperature sliding properties are also reduced. Therefore, the annealing time is preferably 5 seconds or more, and more preferably 20 seconds or more. On the other hand, if the annealing time is 60 seconds or more, the diffusion of Mn is excessively promoted, and as a result, the Mn concentration is reduced at the interface between the scale formed after annealing and the base material. As a result, the formula (ii) cannot be satisfied, and high-temperature sliding properties are reduced. Therefore, the annealing time is preferably less than 60 seconds, and more preferably 50 seconds or less. That is, it is preferable to hold the cold-rolled sheet for the above-mentioned time in the above-mentioned temperature range.
[0085] The cold-rolled sheet may be annealed between passes of cold rolling, and may be annealed by batch annealing or continuous annealing. After annealing, the steel sheet may be cooled at a cooling rate such that the structure of the steel sheet becomes that of austenitic stainless steel.
[0086] 5-5. Pickling process After annealing the cold-rolled sheet, it is preferable to carry out pickling treatment to remove the scale formed by annealing. The pickling method may be any chemical descaling method such as sulfuric acid, nitric hydrofluoric acid, or nitric acid electrolysis, and immersion in a molten alkali salt may be carried out as a pretreatment. The temperature and time conditions of immersion in the molten alkali salt can be appropriately changed depending on the desired properties of the steel sheet. Thereafter, temper rolling and polishing may be carried out as appropriate and necessary.
[0087] 5-6. Processing process The steel plate obtained through the above steps can be processed into a desired part shape by precision machining such as fine blanking to manufacture turbocharger parts. After processing of the parts, special surface treatments such as nitriding or carburizing may be performed to improve high-temperature sliding properties.
[0088] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. EXAMPLES
[0089] After smelting steel having the chemical composition shown in Tables 2 and 3, the following steps were carried out to obtain steel sheets. Specifically, a block of 90 mm length x 150 mm width x 40 mm thickness was cut out from an ingot cast in a 13 kg flat mold. This was hot rolled to 10 mm at 1250°C, hot-rolled sheet annealed at 1150°C for 60 seconds, and then pickled. It was then cold-rolled and annealed under the conditions shown in Tables 4 and 5. It was then pickled to obtain a 5.0 mm thick austenitic stainless steel sheet.
[0090] [Table 2]
[0091] [Table 3]
[0092] (Maximum Mn concentration) The X and Y of the formula (ii) were measured for the obtained steel sheet. For the measurement, a sample having a size of 30 mm length x 30 mm width was cut out, and after degreasing with acetone, a depth analysis was performed from the steel sheet surface to a depth of 10.0 μm in the sheet thickness direction. A glow discharge optical emission spectrometer manufactured by Rigaku was used for the measurement, and the measured elements were Mn, Fe, Cr, Ni, Si, Al, C, N, and O. The maximum Mn concentration in the region from the steel sheet surface to a depth position of 1.0 μm in the sheet thickness direction was taken as X, and the Mn concentration at a depth position of 10.0 μm in the sheet thickness direction from the steel sheet surface was taken as Y. The median value of the formula (ii) was 0.85 to 0.95, and the values not included in the value of ◎ and satisfying the formula (ii) were taken as ◯, and the values not satisfying the formula (ii) were taken as ×.
[0093] (Pin-on-disk method high temperature friction and wear test) For the pin-on-disk high-temperature friction and wear test, a circular disk was taken from each of the obtained steel plates, and a pin was placed so that the tip of the pin was in vertical contact with the disk, and the disk was adjusted so that it would repeatedly undergo friction and wear as the pin rotated around the disk in a furnace at 850°C in air. The bullet-shaped pin had a base diameter of φ6mm, a tip diameter of φ4mm, and a total length of 10mm, while the circular disk was machined to a diameter of φ29mm and a height of 5mm.
[0094] In the above test, the pin and the disk were initially heated without contacting each other, and after holding at 850°C for 1 hour, the pin and the disk were brought into contact in the furnace to start the test. The load was 0.5N, the test distance was 20m, the rotation diameter was 20mm, and the sliding speed was 3.3mm / s. After the test, the wear mark depth of the disk was measured from the disk surface using a laser microscope, and the average value of six points was taken as the average wear mark depth. When the average wear mark depth was 5.0μm or less, it was marked as ◯, and when it was more than 5.0μm, it was marked as ×. As mentioned above, the wear mark depth is the difference between the non-contact part of the pin and the disk and the contact part, and is the largest value.
[0095] A High-Temperature Tribometer manufactured by CSM Instruments was used for the above test, and a VF-8500 manufactured by Keyence was used for measuring the depth of wear marks.
[0096] The results are summarized below and shown in Tables 4 and 5. In Tables 4 and 5, those that do not satisfy the requirements of the present invention and do not satisfy the performance as turbocharger parts are given an overall evaluation of x. The results are summarized below and shown in Tables 4 and 5.
[0097] [Table 4]
[0098] [Table 5] [Industrial Applicability]
[0099] According to the present invention, it is possible to provide an austenitic stainless steel sheet having excellent properties for exhaust parts that require high-temperature sliding properties. In particular, by using the sheet as a turbocharger part among exhaust parts, it is possible to provide a part that satisfies automobile exhaust gas regulations, weight reduction, and improved fuel efficiency. Furthermore, the sheet can be applied not only to exhaust parts for automobiles and motorcycles, but also to parts used in high-temperature environments, particularly high-temperature friction environments, such as various boilers and fuel cell systems.
Claims
1. The chemical composition, in mass%, is C: 0.005-0.30%, Si: 1.00-4.00%, Mn: 0.90-8.00%, P: 0.01-0.05%, S: 0.0001-0.01%, Ni: 5.0 to 15.0%, Cr: 19.50-26.00%, N: 0.02-0.40%, Al: 0.001-0.50%, Cu: 0 to 3.0% (excluding 0.05% or more), REM: 0-0.100%, Mo: 0-2.0%, V: 0 to 1.0%, Ti: 0 to 0.30%, Nb: 0 to 0.30%, B: 0 to 0.005%, Ca: 0-0.010%, W: 0 to 3.0%, Zr: 0 to 0.30%, Sn: 0 to 0.50%, Co: 0 to 0.30%, Mg: 0 to 0.010%, Sb: 0 to 0.50%, Ga: 0-0.30%, Ta: 0 to 1.0%, Hf: 0-1.0%, Bi: 0-0.02%, The balance is Fe and impurities. An austenitic stainless steel sheet satisfying the following formulas (i) and (ii): 11.5≦(Cr+Mn) / (Si+Al)≦15.0...(i) 0.80≦X / Y≦1.00...(ii) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero. Each symbol in the above formula is defined as follows. X: Maximum Mn concentration (mass%) in the region from the surface to a depth of 1.0 μm in the sheet thickness direction Y: Mn concentration (mass%) at a depth of 10.0 μm from the surface in the sheet thickness direction
2. The chemical composition, in mass%, Cu: 0.01 to 3.0% (excluding 0.05% or more), REM: 0.0001-0.100%, Mo: 0.1-2.0%, V: 0.05-1.0%, Ti: 0.005-0.30%, Nb: 0.005-0.30%, B: 0.0002 to 0.005%, Ca: 0.0005-0.010%, W: 0.1-3.0%, Zr: 0.05-0.30%, Sn: 0.01-0.50%, Co: 0.03 to 0.30%, Mg: 0.0002 to 0.010%, Sb: 0.005 to 0.50%, Ga: 0.0002-0.30%, Ta: 0.001 to 1.0%, Hf: 0.001 to 1.0%, and Bi: 0.001-0.02%, The austenitic stainless steel sheet according to claim 1, further comprising one or more selected from the group consisting of:
3. 3. The austenitic stainless steel sheet according to claim 1, wherein when the sheet is held at 850°C in air for 1 hour and then subjected to a pin-on-disk friction and wear test in a furnace at 850°C under conditions of a load of 0.5 N and a test distance of 20 m, the average wear scar depth is 5.0 μm or less.
4. The austenitic stainless steel sheet according to any one of claims 1 to 3, which is used for turbocharger parts.
5. An exhaust part using the austenitic stainless steel sheet according to any one of claims 1 to 4.
6. The method for producing an austenitic stainless steel sheet according to any one of claims 1 to 4, wherein a cold-rolled sheet annealing heat treatment is performed in a temperature range of 1140 to 1250°C for 5 seconds or more and less than 60 seconds.
Citation Information
Patent Citations
Heat resistant austenite stainless steel sheet
JP2016089200A
Austenitic stainless steel sheet for exhaust component excellent in heat resistance and surface smoothness and manufacturing method therefor
JP2017014538A
Austenite-based stainless steel sheet excellent in heat resistance and processability and manufacturing method therefor and exhaust component made from stainless steel
JP2017088928A
Austenitic stainless steel and manufacturing method therefor
JP2017160493A
Stainless steel material for diffusion joining jig
JP2018094620A